AN INTEGRATED APPROACH TO TEACHING LITERATURE AND STUDENTS' LITERARY EXPERIENCE : A Case Study at One Children English Course in Bandung - Fauziah, - (2015)
This study reports an integrated approach to teaching literature and students' literary experience. The use of poetry as the learning material helps learners to make connection in the field of their own experiences. This is important to develop students' knowledge of English. Poetry exposes young learners to meaningful contexts and communicative atmosphere. This study focuses to investigate the approaches employed by the teacher to teaching English through poetry and the impacts of the used of the approaches on students' literary experience. This case study involved an English teacher and nine six-grade students as the participants. Three research instruments, which were classroom observation, interview, and document analysis, were used. Classroom observation data as a primary instrument was triangulated by using interview and document analysis. The results of the study show that the Language-Based Approach (LBA) was the main used approach in this study, followed by Reader-Response Approach (RRA) and Information-Based Approach (IBA). The teacher used these approaches concurrently. Furthermore, the use of the approaches impacts on students' literary experience in term of critical thinking, valuable language skills, and personal development. Key words: An integrated Approach to Teaching Literature, Literary Experience, Teaching Poetry, Teaching English to Young Learners (TEYL) in Indonesia Penelitian ini melaporkan pendekatan terpadu pengajaran sastra dan pengalaman sastra siswa. Penggunaan puisi sebagai bahan pembelajaran membantu peserta didik untuk menghubungkan pengalaman dan pelajaran. Hal ini penting untuk mengembangkan pengetahuan siswa tentang bahasa Inggris. Puisi menghadapkan anak-anak dengan konteks yang bermakna dan suasana komunikatif. Studi ini berfokus untuk menyelidiki pendekatan yang digunakan oleh guru dalam pengajaran Bahasa Inggris melalui puisi dan dampak yang digunakan pendekatan pengalaman sastra siswa. Studi kasus ini melibatkan seorang guru Bahasa Inggris dan sembilan siswa kelas enam sebagai peserta. Tiga instrumen penelitian yang digunakan dalam penelitian ini yaitu observasi kelas, wawancara, dan analisis dokumen. Data observasi kelas sebagai instrumen utama yang di dukung oleh data dari hasil wawancara dan analisis dokumen. Hasil penelitian menunjukkan bahwa Language-Based Approach (LBA) adalah pendekatan yang paling sering digunakan dalam penelitian ini, diikuti oleh Reader-Response Approach (RRA) dan Information-Based Approach (IBA). Guru menggunakan pendekatan ini secara integrasi. Selain itu, penggunaan pendekatan berdampak pada pengalaman sastra siswa dalam hal berpikir kritis, kemampuan berbahasa, dan pengembangan kepribadian. Kata Kunci: Pendekatan terpadu dalam pengajaran Sastra, Literary Experience, Pengajaran puisi, Pengajaran Bahasa Inggris untuk Anak-anak di Indonesia